Trade in Information Technologies and Changes in the Demand for Occupations - Vahagn Jerbashian (Center for Economic Studies and Ifo Institute (CESifo), 2021)
I use data from the World Input-Output Database and show that trade in information technologies (IT) has a significant contribution to the growth in foreign intermediate goods in the 2001-2014 period. China has strongly contributed to the rise in trade in IT and has become one of the major foreign suppliers of IT. I merge these data with the EU KLEMS database and EU Labour Force Survey and obtain a dataset of 12 European countries and 2001-2007 period. I show that IT imports from China are associated with lower IT prices in European countries. The fall in IT prices has increased the demand for high wage occupations and reduced the demand for medium wage occupations. Nearly 25 percent of the variation in the demand for occupations can be attributed to the trade with China.
Keywords: F16; J23; J24; O33; L63; 330; trade; information technologies; China; demand for occupations